Near-peer Mentorship: Promoting Medical Student Research With Resident Pairing - Solomon Oak; Cynthia Glickman; Katherine McMackin (Journal of Medical Education and Curricular Development)
BACKGROUND Obtaining a clinical research mentor is a major barrier for medical students interested in research. OBJECTIVE To increase access to research, a Near-Peer Mentor Program (NPMP) was developed to pair medical students with resident mentors to submit case reports to an annual in-hospital research conference. METHODS Students and residents were recruited via surveys and paired based on students’ specialty interests. Support in the form of templates, instructions and timelines were given. To evaluate the program's impact, we reviewed the number of pairs’ projects at the conference, awards, and who advanced their projects to publications and conferences from 2019 to 2022. RESULTS During the study period, 173 students enrolled. The majority 106 (61.2%) were interested in medical specialties, followed by 47 (27.2%) in surgery and surgical subspecialities, and 20 (11.6%) undecided. All students were paired. One hundred and seventy (98.3%) had projects under resident mentors matching their specialty interests. One hundred and fifty (82.9%) completed the program and submitted a case report to the conference. Years with NPMP led to a 122% (55 in 2019 vs 122 in 2020) and 232% (50 in 2021 vs 166 in 2022) increase in medical student conference posters compared to the previous year without NPMP. In both years, NPMP students won all top 3 awards for best case report. Additionally, 10 pairs produced 6 peer-reviewed publications, 5 conference abstracts, and 2 conference oral presentations as first authors. CONCLUSION The NPMP successfully promoted medical student participation in clinical research. The program substantially increased student poster presentations and subsequent publications and presentations stemming from them.